2001
DOI: 10.1086/317646
|View full text |Cite
|
Sign up to set email alerts
|

Ability of 3 Different Meningococcal C Conjugate Vaccines to Induce Immunologic Memory after a Single Dose in UK Toddlers

Abstract: To test for immunologic memory after a single dose of meningococcal C conjugate (MCC) vaccine in toddlers, 226 children 12-18 months old were randomized to receive 1 of 3 MCC vaccines, with a C polysaccharide booster 6 months later. The protein conjugate was diphtheria mutant toxoid in 2 vaccines (MCC-CRM(197)) and was tetanus toxoid in the third (MCC-TT). One month after the MCC vaccines, 91%-100% of children had serum bactericidal antibody (SBA) titers > or =8, and 89%-100% had a > or =4-fold increase. Geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
120
2
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(141 citation statements)
references
References 16 publications
12
120
2
7
Order By: Relevance
“…Hence, a critical point with regard to the extension of early life immunization strategies is to ensure the quality of induced responses and the duration of protection. Recently, it has been demonstrated that infant immunization with conjugated polysaccharide vaccines can generate antibodies with a progressive avidity increase [26][27][28][29][30]. However, these studies do not allow the comparison of infant data with those obtained following the immunization of older children or adults, because the latter are already naturally primed by carriage or exposure to cross-reacting polysaccharides prior to vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, a critical point with regard to the extension of early life immunization strategies is to ensure the quality of induced responses and the duration of protection. Recently, it has been demonstrated that infant immunization with conjugated polysaccharide vaccines can generate antibodies with a progressive avidity increase [26][27][28][29][30]. However, these studies do not allow the comparison of infant data with those obtained following the immunization of older children or adults, because the latter are already naturally primed by carriage or exposure to cross-reacting polysaccharides prior to vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed in infants indicated a progressive increase of somatic mutation of immunoglobulin genes between 2 and 10 months of age, with evidence for selection only observed from 6 months onwards [24,25]. Avidity maturation was shown to occur following early infant immunization with conjugated polysaccharide vaccines [26][27][28][29][30]. However, it has been reported that following N. meningitidis infection, infants produced specific antibodies of a significantly lower average avidity than older children, which correlated with the absence of bactericidal activity in infant sera [31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover these conjugate vaccines will induce a memory response with a rise of antibody titer after several rounds of Table 1 Box 1 immunization and a booster response several months later . Surprisingly, in older infants and in adults, the same conjugate vaccine [21][22][23][24] does not induce a memory response but a response similar to the one obtained with the plain CPS preparation , even though the [25][26][27][28] response to the conjugate appears in some cases more robust . We have shown that humans display a circulating marginal zone B cell population which is involved in TI response and which diversifies its Ig receptor in the absence of cognate T-B interactions.…”
Section: Paradoxmentioning
confidence: 99%
“…Following promising results in infants vaccinated under the UK 2/3/4 month schedule [11][12][13], the DH initiated further clinical trials to answer key policy-related questions. These trials determined the schedule to be used for catch-up immunisation of older age groups [14], the effect of prior vaccination with plain meningococcal C polysaccharide used for outbreak control on the response to MCC vaccines [15][16][17], and the compatibility of MCC vaccines when given at the same time as other vaccines used in the UK schedule, in particular diphtheria and tetanus vaccines which are similar to the carrier proteins in the MCC vaccines [1]. These DH-funded trials were complemented by manufacturer-sponsored trials designed to provide data required by the licensing authority, such as batch-tobatch variation [18] and the safety and immunogenicity of MCC vaccines compared with the licensed plain polysaccharide vaccine [19].…”
Section: Pre-licensure Studiesmentioning
confidence: 99%